2023
DOI: 10.1001/jamanetworkopen.2022.55110
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Best Practices to Improve Diversity, Equity, and Inclusion Among US Graduate Medical Education Programs

Abstract: ImportanceClosing the diversity gap is critical to ensure equity in medical education and health care quality. Nevertheless, evidence-based strategies and best practices to improve diversity, equity, and inclusion (DEI) in the biomedical workforce remain poorly understood and underused. To improve the culture of DEI in graduate medical education (GME), in 2020 the Accreditation Council of Graduate Medical Education (ACGME) launched the Barbara Ross-Lee, DO, Diversity, Equity, and Inclusion Award to recognize e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Although the LCME’s 2009 diversity standards coincided with an increase in female, Black, and Hispanic matriculants, it remains unclear whether this increase was linked to the new standards . The decreasing trend currently seen in medical programs suggests that the LCME standard related to diversity is not sufficient to address the need for more diversity in the health professions programs . For medical programs, low Medical College Admission Test scores, low grade point averages, and poor science preparation have been identified as barriers to pursuing a medical career by premedical students from URM groups and to the recruitment of prospective students from URM groups .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the LCME’s 2009 diversity standards coincided with an increase in female, Black, and Hispanic matriculants, it remains unclear whether this increase was linked to the new standards . The decreasing trend currently seen in medical programs suggests that the LCME standard related to diversity is not sufficient to address the need for more diversity in the health professions programs . For medical programs, low Medical College Admission Test scores, low grade point averages, and poor science preparation have been identified as barriers to pursuing a medical career by premedical students from URM groups and to the recruitment of prospective students from URM groups .…”
Section: Discussionmentioning
confidence: 99%
“…Myriad efforts have sought to expand the applicant pool and promote equitable recruitment and selection processes, but few have focused on enhancing student inclusion . Research by Nwokolo et al highlights a concerning trend: a widening gap between matriculation and graduation rates for medical students from URM groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 In response, as one part of the solution, increased attention has been given to addressing diversity, equity, and inclusion (DEI) in graduate medical education in recent years. 7 , 8 In 2020 the Accreditation Council for Graduate Medical Education (ACGME) released updated Common Program Requirements, which require all residency programs to address DEI. 9 Many programs are struggling to incorporate the requirement to address DEI; a 2020 survey from the Association of Family Medicine Residency Directors (AFMRD) Diversity and Health Equity (DHE) Committee indicated that 50% of family medicine program directors were not confident implementing the common program requirement change pertaining to diversity.…”
Section: Introductionmentioning
confidence: 99%